Applying the technique of volume‐modulated arc radiotherapy to upper esophageal carcinoma - Ma, Pan (J Appl Clin Med Phys, 2014)
This study aims to evaluate the possibility of using the technique of volume‐modulated arc therapy (VMAT) to combine the advantages of simplified intensity ‐ modulated radiation therapy (sIMRT) with that of regular intensity‐modulated radiation therapy (IMRT) in upper esophageal cancer. Ten patients with upper esophageal carcinoma were randomly chosen in this retrospective study. sIMRT, IMRT, and VMAT plans were generated to deliver 60 Gy in 30 fractions to the planning target volume (PTV). For each patient, with the same clinical requirements (target dose prescription, and dose/dose‐volume constraints to organs at risk (OARs)), three plans were designed for sIMRT (five equispaced coplanar beams), IMRT (seven equispaced coplanar beams), and VMAT (two complete arcs). Comparisons were performed for dosimetric parameters of PTV and of OARs (lungs, spinal cord PRV, heart and normal tissue (NT)). All the plans were delivered to a phantom to evaluate the treatment time. The Wilcoxon matched‐pairs, signed‐rank test was used for intragroup comparison. For all patients, compared to sIMRT plans, VMAT plans statistically provide: a) significant improvement in HI and CI for PTV; b) significant decrease in delivery time, lung V20, MLD, heart V30 and spinal cord PRV D1cc; c) significant increase in NT V5; and d) no significant reduction in lung V5, V10, and heart MD. For all patients, compared to IMRT plans, VMAT plans statistically provide: a) significant improvement in CI for PTV; b) significant decrease in delivery time, lung V20, MLD, NT and spinal cord PRV D1cc; c) significant increase in NT V5; and d) no significant reduction in HI for PTV, lung V5, V10, heart V30 and heart MD. For patients with upper esophageal carcinoma, using VMAT significantly reduces the delivery time and the dose to the lungs compared with IMRT, and consequently saves as much treatment time as sIMRT. Considering those significant advantages, compared to sIMRT and IMRT, VMAT is the first choice of radiotherapy techniques for upper esophageal carcinoma. PACS number: 87.55. D‐